2004
DOI: 10.1038/sj.bdj.4811178
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of brackets bonded with an adhesion promoter

Abstract: Materials and methods Enhance-L.C. was used with one of the manufacturer's recommended adhesives, Light-Bond, and with a second from another manufacturer, Transbond-XT. One hundred premolars were divided into four groups of 25 premolars: 1)Transbond-XT, 2) Transbond-XT/Enhance-L.C., 3) Light-Bond, 4) Light-Bond/Enhance-L.C. Main outcome measures Shear bond strength was evaluated with a universal test machine and the adhesive remaining after debonding was determined using image analysis equipment. Results Enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1
9

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 12 publications
6
45
1
9
Order By: Relevance
“…However, controversy over the results obtained with these products persists. Some studies have observed bond strength values similar to those achieved using the traditional acid-etch technique (5). Others have found that the bond strength of self-etching primers was lower (6) than when conventional procedures were followed.…”
Section: Introductionmentioning
confidence: 85%
“…However, controversy over the results obtained with these products persists. Some studies have observed bond strength values similar to those achieved using the traditional acid-etch technique (5). Others have found that the bond strength of self-etching primers was lower (6) than when conventional procedures were followed.…”
Section: Introductionmentioning
confidence: 85%
“…27,28,30 Self etching primer systems have also been reported to produce good ARI scores as compared to traditional acid-etch technique. [46][47][48] The removal of the residual adhesive can be accomplished via debonding pliers, ultrasonic scaler, high-speed tungsten carbide bur or by low-speed tungsten carbide bur Debonding pliers cause the least enamel loss, however more residual adhesive remained. 48 The least enamel loss was reported to occur with self-etching primer and after enamel clean-up with a slow-speed tungsten carbide bur with water.…”
Section: Enamel Prophylaxis and Fluoride Exposure (Prior To Bonding)mentioning
confidence: 99%
“…The use of conventional etching and priming is discouraged since phosphoric acid, may cause more enamel loss than self etching primers. 47,48 This might reduce adhesion to hypomineralized enamel, because of inadequate micro-tag formation, consequential to the formation of little intercrystal porosity. 19 Other possible effects of severe enamel loss are: increased micro leakage around brackets with potential connection between enamel surface and the subsurface opacities, which might produce either an objectionable color change following extrinsic staining or a higher risk for demineralization and postoperative sensitivity.…”
Section: Modifications Necessary For Adhesion To Hypomineralized Enamelmentioning
confidence: 99%
“…[12][13][14] While these conditioners were initially developed for use on dentin, researchers have determined that adhesive systems combining conditioning and priming can be successfully used to bond orthodontic brackets to enamel. [15][16][17] It has been demonstrated that SBSs of brackets bonded using different self-etch primers (SEPs) were not significantly different from brackets bonded with the conventional acid-etch technique. 15,17 As each SEP is unique in formulation and conditioning aggressiveness, the manufacturers of these products typically recommend using a specific conditioning time and method to achieve optimal results.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] It has been demonstrated that SBSs of brackets bonded using different self-etch primers (SEPs) were not significantly different from brackets bonded with the conventional acid-etch technique. 15,17 As each SEP is unique in formulation and conditioning aggressiveness, the manufacturers of these products typically recommend using a specific conditioning time and method to achieve optimal results. While the recommended protocols usually provide satisfactory results, it was reported that significantly less leakage was found in class V restorations when an SEP was used for twice the manufacturer's recommended application time.…”
Section: Introductionmentioning
confidence: 99%